Correlation between complications during delivery and neonatal mortality: Data analysis of Indonesia Demographic and Health Survey (IDHS) 2017 - Noor Anisa; Andari Wuri Astuti; Mohammad Hakimi (Faculty of Medicine, Universitas Islam Indonesia, 2022)
Background: Neonatal mortality is a death that occurs during the first twenty-eight days of life after a baby is born. Based on Indonesia Demographic and Health Survey (IDHS data) in 2017, there was a decrease in neonatal mortality between 2012 – 2017, but this has not yet reached the SDG's target of 12 deaths per 1,000 live births. Complications during childbirth are one of maternal factors that directly cause pain and death to a mother and her or newborn due to some disorders resulting from childbirth. One of the factors that can influence neonatal mortality is complications during delivery.Objective: This study aims to observe correlation between complications during childbirth and neonatal mortality. Also, this is to reveal the neonatal mortality rate in children born from 2012-2017 in Indonesia after controlling for all confounding.Methods: This was a cross-sectional study with an analytical observational approach using secondary data from the IDHS 2017. Its samples were women of childbearing age (15-49 years) who have been married and gave birth, with the last birth data of 5 years prior to the survey. Its inclusion criteria were children who were born in 2012-2017 and were not twin-birth as big as 15.357. The sample selection used total sampling, and the obtained data were analysed by univariate, bivariate, and multivariate analysis using multiple logistic regression.Results: The final model indicated that there was a significant relationship between the complications during delivery and neonatal mortality after controlling by variables of age, ANC visits, baby's birth weight, and baby's gender on neonatal mortality. PR 3,90 (95% C.I; 2.467 – 6.187).Conclusion: The results revealed that there was an influence of childbirth complications, maternal age, ANC visits, baby's birth weight, and baby's gender on neonatal mortality.